2014
DOI: 10.1016/j.chemosphere.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochemical patterns of calcium, zinc, and potassium related to internal factors detected by energy dispersive X-ray fluorescence (EDXRF)

Abstract: Energy dispersive X-ray fluorescence (EDXRF) provides highly sensitive and precise spatial resolution of cation content in individual annual growth rings in trees. The sensitivity and precision have prompted successful applications to forensic dendrochemistry and the timing of environmental releases of contaminants. These applications have highlighted the need to distinguish dendrochemical effects of internal processes from environmental contamination. Calcium, potassium, and zinc are three marker cations that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
4
16
1
Order By: Relevance
“…More recently, Dredge et al (2015) reported that elastic (Rayleigh) scatter maps from XRF scans conducted at 18.5 keV revealed the wood grain of the underlying oak support of the AGNSW Henry VIII portrait. This observation supported reported associations between variation in intra-annual tree-ring structure and XRF-derived elemental concentrations (Scharnweber et al 2016), and between XRF-imaged grain and anatomically defined tree-ring boundaries (Smith et al 2014). These associations suggest high-resolution XRF imagery may be a source of non-invasive dendrochronological as well as artistic data.…”
Section: Introductionsupporting
confidence: 83%
“…More recently, Dredge et al (2015) reported that elastic (Rayleigh) scatter maps from XRF scans conducted at 18.5 keV revealed the wood grain of the underlying oak support of the AGNSW Henry VIII portrait. This observation supported reported associations between variation in intra-annual tree-ring structure and XRF-derived elemental concentrations (Scharnweber et al 2016), and between XRF-imaged grain and anatomically defined tree-ring boundaries (Smith et al 2014). These associations suggest high-resolution XRF imagery may be a source of non-invasive dendrochronological as well as artistic data.…”
Section: Introductionsupporting
confidence: 83%
“…Many techniques have been used to analyse the matrix and trace elements including the toxic heavy metal content of tree rings, including XRF (x-ray fluorescence) spectrometry (MacDonald et al 2011, Smith et al 2014, Scharnweber et al 2016, XCT (x-ray computed tomography -Van Den Bulcke et al 2014), PIXE (particle-induced xray emission) analysis (Glass et al 1993, Calva-Vazquez et al 2006, EMPA (electron microprobe analyzer - Kuczumow 2004), XRD (x-ray diffraction), IR (infrared spectroscopy), SIMS (secondary ion mass spectrometry), and LA-ICP-MS, etc. (Watt et al 2007, Vašinová-Galiová et al 2013, Sensula et al 2017, Perone et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Heartwood formation is also an active process and involves the movement of nutrients (Spicer 2005 ), reflecting the fact that elemental concentrations in sapwood and heartwood often differ (Meerts 2002 ). Changes along the sapwood/heartwood boundary can be sharp, as seen in the steep decline of K concentrations from sapwood to heartwood in Quercus robur (Smith et al 2014 ) or the peak of Ca at the sapwood/heartwood boundary in Miliusa velutina (Poussart et al 2006 ). As long as wood is live sapwood, many active processes can affect the deposition, exchange and transport (including radially) of elements.…”
Section: Introductionmentioning
confidence: 99%
“…Since primary cell walls have higher concentrations of pectins than secondary walls (Sarkar et al 2009 ), cell types with thick secondary walls such as fibers should have a lower proportion of pectins and cations binding to these than thin-walled parenchyma cells. Mineral inclusions in wood have high concentrations of specific elements, they are not distributed uniformly and can be seen in micro-density measurements (Vansteenkiste et al 2007 ) and chemically analyzed by energy-dispersive X-ray fluorescence (Smith et al 2014 ). The concentration of nutrients essential for the functioning of living cells will depend on the proportion of living (parenchyma) cells in wood, which often decreases from the cambium onwards and is zero in heartwood.…”
Section: Introductionmentioning
confidence: 99%